Optimasi Performa Web Service melalui Penguatan Logika Asynchronous JavaScript for Server-Side Development pada Pelatihan Nasional Bangkit 2024 Batch 2 - Marzuki Pilliang; Afifah Khaerani A (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Web service efficiency in handling concurrent requests is a crucial parameter in large-scale application development. Server-side JavaScript, through Node.js, offers a solution via non-blocking architecture, yet its effectiveness heavily depends on the precision of asynchronous logic implementation by the developer. This Community Service (PkM) activity aims to optimize students' technical abilities in building high-performance web services within the 2024 Bangkit Academy Batch 2 Program. The implementation method was conducted through a national online workshop emphasizing asynchronous design patterns, event loop management, and race condition mitigation techniques. The results indicate an increase in participants' capabilities to reduce system latency through the efficient use of Promises and Async-Await. Technical evaluations prove that strengthening this logic not only enhances code execution speed but also ensures the reliability of web services in handling intensive workloads according to global financial and technology industry standards.